Enhancing Project Management through Outsourcing: Transforming Growth in Information Technology (IT) - Hossain, Mohammad Ikbal; Sultana, Tanzina; Islam, Mohammad Nahid Ul; Akther, Afroja; Sarpong, Alexander Fosu; Akter, Fatema (Journal of Knowledge Management Practice, 2025)
Transformational outsourcing is redefined as a strategic evolution from cost-centric models to deep, collaborative partnerships that drive organizational innovation and change. This approach highlights the importance for IT firms to engage in outsourcing that not only achieves cost efficiency but also promotes strategic growth and competitive advantage, focusing on leveraging core competencies. The analysis explores into the advantages and potential downsides of IT outsourcing, stressing the necessity for meticulous planning and execution to overcome challenges such as vendor selection, communication gaps, and risk management, thereby enabling IT companies to boost efficiency, spur innovation, and maintain competitiveness in the fast-paced tech environment.
Keywords: knowledge management; transformational outsourcing; strategic evolution; collaborative partnerships; organizational innovation; cost efficiency; core competencies